2021
DOI: 10.1177/2473974x211041124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radiofrequency Neurolysis on the Symptoms of Chronic Rhinitis: A Randomized Controlled Trial

Abstract: Objective To determine the safety and efficacy of temperature-controlled radiofrequency (RF) neurolysis of the posterior nasal nerve (PNN) area for the treatment of chronic rhinitis. Study Design A multicenter, prospective, single-blinded, randomized controlled trial, in which the control arm underwent a sham procedure. Setting Sixteen otolaryngology centers. Methods Patients with 24-hour reflective Total Nasal Symptom Score (rTNSS) ≥6, including moderate to severe rhinorrhea and mild to severe congestion, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(105 citation statements)
references
References 13 publications
10
95
0
Order By: Relevance
“… 7 , 8 TCRF neurolysis of the PNN demonstrated superiority over a sham procedure at 3 months postprocedure in a randomized controlled trial. 9 In a separate single-arm study, the procedure showed a significant reduction in rhinitis symptom burden (efficacy) through 12 months, as measured by the reflective total nasal symptom score (rTNSS). 10 Here, we report safety and efficacy results of long-term follow-up of that same single-arm study at 24 months, in addition to patient quality of life (QoL) data and the extent of patient satisfaction with the procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 TCRF neurolysis of the PNN demonstrated superiority over a sham procedure at 3 months postprocedure in a randomized controlled trial. 9 In a separate single-arm study, the procedure showed a significant reduction in rhinitis symptom burden (efficacy) through 12 months, as measured by the reflective total nasal symptom score (rTNSS). 10 Here, we report safety and efficacy results of long-term follow-up of that same single-arm study at 24 months, in addition to patient quality of life (QoL) data and the extent of patient satisfaction with the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This product has similarities to RhinAer (Aerin Medical) and Clarifix (Stryker) in direct ablative targeting of the posterior nasal nerve. 9 , 10 The primary differences relate to the geometry of the electrode array. The device is operated via a slider and an activation switch on the handle.…”
Section: Discussionmentioning
confidence: 99%
“…Del Signore et al used variable block size distribution by site with a 1:1 allocation [15]. Stolovitzky et al used a 2:1 site-stratified block randomization [16]. In both RCTs the patients were blinded to their assignment and blindfolded during the treatment.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All were carried out in the USA and six out of the eight had industry sponsorship. Follow up periods varied between 3 months [13,14,15,16], 9 months [17], 12 months [18,19], and 24 months [20].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation